2011
DOI: 10.1111/j.1600-0838.2011.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different pedalling techniques on muscle fatigue and mechanical efficiency during prolonged cycling

Abstract: The present study aimed to test the influence of the pedalling technique on the occurrence of muscular fatigue and on the energetic demand during prolonged constant-load cycling exercise. Subjects performed two prolonged (45 min) cycling sessions at constant intensity (75% of maximal aerobic power). In a random order, participants cycled either with their preferred technique (PT) during one session or were helped by a visual force-feedback to modify their pedalling pattern during the other one (FB). Index of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…With fatigue, significance of horizontal elements of pedaling technique increases. At finish effectiveness of cyclists resulting forces increases [27]. Our results concord well with other data and are confirmed by them [2,3,6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With fatigue, significance of horizontal elements of pedaling technique increases. At finish effectiveness of cyclists resulting forces increases [27]. Our results concord well with other data and are confirmed by them [2,3,6].…”
Section: Discussionsupporting
confidence: 91%
“…Most specialists mark out conventionally start, distance and finish segments [19,27]. Such division is a result of pedagogic observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mentioned by us changes in pedaling structure in period of evident fatigue witness about weakening of muscles' contraction function and emersion of discoordination in nervous centers' functioning [11,21,25,28]. In opinion of some authors [1,6,14,17], increase of bio-potential oscillations' amplitude and reduction of frequency characteristics of electric myogram (like in our researches) witness about involvement of additional motor units in active state [7,14,29].…”
Section: Discussionsupporting
confidence: 62%
“…A number of studies have investigated the laboratory practice of recording these measures [19,23,28,32], the impact of training status and interventions [1,7,15,16,17,26], gender [3,18], and adaptations that could result in improved efficiency [5,9,12,24,25,33]. Furthermore, it is suggested that there are potential performance benefits of improved efficiency as Jeukendrup and& Martin [21] calculated that increasing gross efficiency by 1%, for a 70 kg cyclist who can maintain a power output of 400 W for 1 h, would result in a 48s improvement for a timetrial over 40 km.…”
Section: Introductionmentioning
confidence: 99%